The effect of extra virgin olive oil (EVOO) on fat mass and fat-free mass for breastfeeding mothers (0-24 months) in Makassar City, Indonesia - Sri W. Abidin; Citrakesumasari Citrakesumasari; Burhanuddin Bahar; Nurhaedar Jafar; Healthy Hidayanti; Veni Hadju (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Extra Virgin Olive Oil (EVOO) is a fat source classified as monounsaturated fatty acid. Previous studies have shown that 47.5% of breastfeeding mothers have less fat intake when compared to the Adequacy of Nutrition Rate (RDA). EVOO consumption can improve the composition of breast milk. However, no research has been found regarding the body composition of breastfeeding mothers after consuming EVOO. This study aims to determine the effect of EVOO on the body composition of breastfeeding mothers 0-24 months. MATERIALS AND METHODS: The study was conducted at the Sudiang Raya and Tamalanrea Health Centers in Makassar City with a randomized clinical trial design from January to February 2023. The sample was breastfeeding mothers 0-24 months divided into the intervention group (EVOO and Nutrition Education, n = 17) and the control (Nutrition Education, n = 17). Instruments with Bioelectrical Impedence Analysis tools. Data analysis using t-test. RESULTS: The sample is breastfeeding mothers aged between ≤19 and >35 years. The results of the analysis showed that the average pre-post test, % fat mass (FM) P = 0.426 and % fat free mass (FFM) P = 0.508 (P > 0.05), meant that there was no significant difference. Between the two groups there was no significant difference at the end of the study, %FM P = 0.469 and %FFM P = 0.529 (P > 0.05). CONCLUSIONS: In the intervention group that was given EVOO, it was possible to maintain%FM and%FFM in the normal percentage range, while in the control group, there was a decrease from the normal to less/low range.